Sedation/Analgesia Administration Practice Varies according to Endoscopy Facility (Hospital- or Office-Based) Setting: Results from a Nationwide Survey in Greece. (5th October 2020) - Tziatzios, Georgios; Samonakis, Dimitrios N.; Tsionis, Theocharis; Goulas, Spyridon; Christodoulou, Dimitrios; Triantafyllou, Konstantinos
Abstract : Objectives . To examine the impact of endoscopy setting (hospital-based vs. office-based) on sedation/analgesia administration and to provide nationwide data on monitoring practices among Greek gastroenterologists in real-world settings. Material and Methods . A web-based survey regarding sedation/analgesia rates and monitoring practices during endoscopy either in a hospital-based or in an office-based setting was disseminated to the members of the Hellenic Society of Gastroenterology and Professional Association of Gastroenterologists. Participants were asked to complete a questionnaire, which consisted of 35 items, stratified into 4 sections: demographics, preprocedure (informed consent, initial patient evaluation), intraprocedure (monitoring practices, sedative agents' administration rate), and postprocedure practices (recovery). Results . 211 individuals responded (response rate: 40.3%). Propofol use was significantly higher in the private hospital compared to the public hospital and the office-based setting for esophagogastroduodenoscopy (EGD) (85.8% vs. 19.5% vs. 10.5%, p < 0.0001 ) and colonoscopy (88.2% vs. 20.1% vs. 9.4%, p < 0.0001 ). This effect was not detected for midazolam, pethidine, and fentanyl use. Endoscopists themselves administered the medications in most cases. However, a significant contribution of anesthesiology sedation/analgesia provision was detected in private hospitals (14.7% vs. 2.8% vs. 2.4%, p < 0.001 ) compared to the other settings. Only 35.2% of the private offices have a separate recovery room, compared to 80.4% and 58.7% of the private hospital- and public hospital-based facilities, respectively, while the nursing personnel monitored patients' recovery in most of the cases. Participants were familiar with airway management techniques (83.9% with bag valve mask and 23.2% with endotracheal intubation), while 49.7% and 21.8% had received Basic Life Support (BLS) and Advanced Life Support (ALS) training, respectively. Conclusion . The private hospital-based setting is associated with higher propofol sedation administration both for EGD and for colonoscopy. Greek endoscopists are adequately trained in airway management techniques.